The Role of School-Society Collaboration in the Development of Primary Schools - Ugobueze, Ann Ngozi (Journal of Indonesian Primary School, 2024)
This study focused on the role of school-society collaboration in the development of primary schools, emphasizing its influence on educational outcomes and community advancement. It provides an overview of school-society collaboration, tracing its historical evolution and theoretical foundations, while highlighting its significance in fostering robust educational frameworks. The study identifies key stakeholders—families, local communities, governments, private sector entities, and NGOs—and examines their contributions to the collaborative ecosystem. Mechanisms facilitating collaboration, such as parent-teacher associations, community programs, and partnerships with local businesses, are analyzed to illustrate their impact on educational improvement. The benefits of such collaboration include enhanced student performance, social and emotional development, and strengthened community identity and cohesion. However, challenges such as socioeconomic barriers, communication gaps, and policy-related constraints are acknowledged, necessitating targeted interventions. Recommendations focus on strengthening partnerships, promoting inclusivity, developing sustainable models, and building stakeholder capacity to ensure effective collaboration. This study highlighted the importance of integrating collective responsibility in advancing primary education and fostering a shared commitment to societal development.